Time, space, and the unknown : Maasai configurations of power and providence - Spencer, Paul, 1932- (Routledge, 2003)
Time, Space and the Unknown follows on from The Maasai of Matapoto and The Samburu to show how uncertainty and misfortune influence the social life of the Maasai.